Prevalence of Anemia in Patients Presenting with Febrile Fits - Khawaja Abrar Ahmed, Manzoor Ali Khan, Ishtiaq Ahmed Mughal, Syed Zakir Hussain Shah, Mohsna Saeed Zia, Arzoo Idrees (Pakistan Journal of Medical & Health Sciences, 2022)
Objective: To determine the prevalence of iron deficiency anemia in children with febrile fits. Study Design: Prospective study Place and Duration of Study: Paediatric Medicine, Abbas Institute of Medical Sciences (AIMS) Muzafarabad, AJ Kashmir from 01-04-2021 to 31-03-2022. Methodology: Ninety patients within the age limit of 6 months to 5 years were enrolled. The inclusion criteria were based on the all the children suffering from febrile fits. The enrolled patients’ blood sample comprising of 4cc was pooled and sent for biochemical analysis of hemoglobulin, serum ferritin as well as red cell distribution width. The results of each patients’ reports were used for analysis of their anemia status. Results: The mean age of the patients was 2.6±1.5 years with more boys suffering from febrile fits.. Most of the children belonged to the age group of 1-3 years. The biochemical blood analysis reports revealed that there were 56.25% those children who were suffering from hemoglobulin level less than 10g/dl. The overall prevalence of iron deficiency anemia was found to be 33.75 among boys while 25% within the girls. Conclusion: There is a percentage of iron deficiency anemia as 58.75% in children with febrile fit. Key Words: Prevalence, Anemia, Febrile fits.